The Wild Palms - Faulkner, William (London Vintage Books, 2000)
In New Orleans in 1937, a man and woman embark on a headlong flight into the wilderness of illicit passion, fleeing her husband and the temptations of respectability. In Mississippi ten years earlier, a convict sets forth across a flooded river, risking his one chance at freedom to rescue a pregnant woman. From these separate stories Faulkner composes a symphony of deliverance and damnation, survival and self-sacrifice, a novel in which elemental danger is juxtaposed with fatal injuries of the spirit.
English Fiction.
Keywords: Man-woman relationships -- Floods -- Mississippi River Valley